Protecting the Religious Belief: A Study on the Blasphemy Laws Across Jurisdictions and Religions - Ali, Mahrus; Al-Fahad, Hamad Faisal; Prabowo, M Shidqon; Wibawa, I Putu Sastra; Harefa, Beniharmoni; Sanjaya, Aditya Wiguna (Contemporary Issues on Interfaith Law and Society, 2025)
The purpose of this article is to examines legal and religious dimensions of blasphemy in the provisions of Penal Code of Indonesia, Kuwaiti law correspond to the established principles of Islamic, Christianity, and Hinduism. This is through employing a critical and comparative approach, the study compares the foundational of Penal Code of Indonesia and the Kuwaiti legislation as well as Islamic Sharia, Christianity and Hinduism, identifying areas of overlap in criminalizing offenses against religious belief. The paper found that the Penal Code of Indonesia criminalizes incitement or coercion aimed at making others abandon their religion or belief through violence or threats, while Kuwaiti law largely reflects the Sharia based prohibition of conduct deemed offensive to sacred values. The underlying philosophies behind the criminalization of blasphemy in Islamic Sharia, Penal Code Kuwaiti law, may differ in their foundational justifications, they join on a shared notion, to protect religious thoughts and prevent the incitement of discord and hatred under freedom of expression. From the Christianity perspective, Christians are taught not only to forgive, pray for, and bless the offender, but also, if needed, to pursue legal avenues as provided by national laws. Hinduism places greater importance on maintaining fraternal relationships among humans being than on defending the honour of the religion or its deities. If an act is deemed blasphemous according to the law of the state, the recommended course of action in Hinduism is to restore spiritual balance through a ritual of atonement known as Prayascitta.